Role of venous blood gases in hypercapnic respiratory failure chronic obstructive pulmonary disease patients presenting to the emergency department. Issue 7 (11th July 2019) - Wong, Eric Ka Cheong; Lee, Philip (Cheuk Shing); Ansary, Saidul; Asha, Stephen; Wong, Keith K. H.; Yee, Brendon J.; Ng, Andrew T.
Abstract: Background: Many patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have type 2 respiratory failure (T2RF). Often arterial blood gases are not performed and correlation with venous blood gases (VBG) is controversial. The venous pH and bicarbonate (HCO3 ) are useful, but VBG pCO2 (PvCO2 ) is considered too unpredictable. Aim: To examine the utility of VBG in this cohort of patients. Methods: A prospective study of AECOPD patients with T2RF presenting to the emergency department was performed. Patients being considered for non‐invasive ventilation and who required an arterial blood gas were invited to participate. A subsequent VBG was also taken, and Bland–Altman plots were used for analysis. Results: Sixty‐three patients were included in this study. The limits of agreement for pH and HCO3 were narrow. Wider limits of agreement with a systematic bias of 7.7 mmHg were noted with pCO2 . Conclusions: The utility of VBG pH and HCO3 was again demonstrated. VBG pCO2 in this cohort of patients may have a role in the assessment of patients with AECOPD. Further study is needed on the possible role of VBG in the management of such patients with T2RF particularly those using non‐invasive ventilation.